Cognitive scientists opportunities - Русяєва, Т.Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The paper proposes the questions, related to definition of conditions of realization cognitive possibilities of scientists in scientific activity.